Utilization of Open-Ended Problems Model to Analyze Students’ Creative Thinking Ability on Electrochemistry Lesson - Humaeroh, Ika; Irwandi, Dedi; Saridewi, Nanda (Jurnal Penelitian dan Pembelajaran IPA, 2018)
The objective of the present research is to study students’ achievement in creative thinking ability and to determine the level of their ability in creative thinking in electrochemistry through open-ended problems model. The method used in this research is Descriptive Study. The sample of this research is 12th grade students majoring in Science of SMAN 3 South Tangerang which consist of 28 students. The sample taken are  students of 12th  grade majoring in science from selected classes; they have higher scores in daily test compared to 4 other classes. This was simply for convenience of studying the learning process and the implementation of open-ended model problem in this study. The data of this research was acquired from observation sheet, test and interview. In this research the achievement of student’s creative thinking ability was focused on three aspects of creative thinking: fluency, flexibility and originality. The result showed that student’s achievement on fluency was good, flexibility was average and originality was average. Meanwhile, the open-ended test result showed that student’s achievement on fluency was good, flexibility was average and originality was also average. Level of student’s ability in creative thinking was categorized as very poor, poor and average. Number of students in each category was 10 students (35.71%) in very poor category, 17 students (60.71%) in poor category, and 1 student (3.57%) in average category.